RETAINER AND THERMAL DISPLACEMENT APPARATUS FOR ELECTRONIC COMPONENTS - CALDER, JAMES, CHARLES (2009)
Retainers (10) are described that comprise at least one center body component (12) comprising a plurality of center body troughs (14, 16), and at least one compatible component (20, 24) comprising a plurality of compatible troughs. (22, 26), wherein at least part of the plurality of the compatible troughs couple with at least part of the plurality of center body troughs. In addition, thermal displacement devices are described that incorporate at least one retainers and at least one additional component, wherein the at least one retainer is coupled at least in part to the at least one additional component through a contact area or a substrate, surface or combination thereof, wherein the at least one retainer is coupled with the substrate, surface or combination thereof through a contact area. La présente invention concerne des éléments de retenue qui comprennent au moins un composant de corps central comprenant une pluralité de creux de corps central, et au moins un composant comportant comprenant une pluralité de creux compatible, au moins une partie de la pluralité de creux se couplant à au moins une partie de la pluralité de creux de corps central. En outre, des dispositifs de déplacement thermique sont décrits, lesquels incorporent au moins un élément de retenue et au moins un composant supplémentaire, le ou les éléments de retenue étant couplés au moins en partie à un ou plusieurs composants supplémentaires à travers une zone de contact ou un substrat, une surface ou une combinaison de ceux-ci, le ou les éléments de retenue étant couplés avec le substrat, la surface ou la combinaison de ceux-ci à travers une zone de contact.